2018
DOI: 10.1177/2050312118813283
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of intranasal droperidol in volunteers characterised via population modelling

Abstract: Background:Droperidol is used parenterally to treat nausea and vomiting, migraine and acute behavioural disturbance. Intranasal use is not reported for droperidol. Intranasal drug administration reduces need for intravenous line placement and risk of needle-stick.Objective:To model population pharmacokinetics of intranasal droperidol.Method:Single doses of intranasal and intravenous droperidol (0.02 mg/kg) were studied in an open-label crossover-trial in seven volunteers with a 1-week washout period. Blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has been shown that low dose intranasal (IN) droperidol has a peak serum level within 1 h of administration and that it approximates the levels reached using low dose i.v. droperidol 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that low dose intranasal (IN) droperidol has a peak serum level within 1 h of administration and that it approximates the levels reached using low dose i.v. droperidol 8 …”
Section: Introductionmentioning
confidence: 99%
“…droperidol. 8 Our department has been successfully using IN droperidol to treat headache for several years. To our knowledge, there have been no published studies of IN droperidol for the treatment of any disease.…”
Section: Introductionmentioning
confidence: 99%